1992
DOI: 10.1111/j.1346-8138.1992.tb03251.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Planus Annularis: An Immunohistochemical Study

Abstract: Lichen planus annularis is a relatively rare skin manifestation of lichen planus. The mechanisms in the formation of annular lesions are not fully understood. We reported here a 57-year-old female with this disease. The eruption initially occurred as lichen-papules, then enlarged (bean-sized, umbilicated small plaques), and finally developed annular manifestations. We performed immunohistochemical examinations of specimens taken from different types of eruptions. In all specimens, HLA-DR was expressed in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…In the focal cellular infiltrate in the salivary glands, which is the specific feature of Sjogren-type sicca syndrome, CD45RO+ cells were also prominent in most of the foci, and HLA-DR an tigens were expressed mainly in those foci. These results seem to agree with those of previous immunopathologic studies of LP (15,22) and Sjogren's syndrome (14,23), suggesting that the cellular infiltration of LP and Sjogren-type sicca syndrome in this case may be attributable to a common pathogenetic mechanism. This suggestion may be supported by the clinical data showing that the normalization of high serum amylase level, in which salivary amylase predominated, paralleled the improvement in the oral LP.…”
Section: Discussionsupporting
confidence: 94%
“…In the focal cellular infiltrate in the salivary glands, which is the specific feature of Sjogren-type sicca syndrome, CD45RO+ cells were also prominent in most of the foci, and HLA-DR an tigens were expressed mainly in those foci. These results seem to agree with those of previous immunopathologic studies of LP (15,22) and Sjogren's syndrome (14,23), suggesting that the cellular infiltration of LP and Sjogren-type sicca syndrome in this case may be attributable to a common pathogenetic mechanism. This suggestion may be supported by the clinical data showing that the normalization of high serum amylase level, in which salivary amylase predominated, paralleled the improvement in the oral LP.…”
Section: Discussionsupporting
confidence: 94%
“…Although the mechanism in the formation of annular lesions in lichen planus is not fully understood, recent immunohistochemi cal studies have suggested that intercellular adhesion mole cule 1 expression in the peripheral kératinocytes of active lesions of annular lichen planus may be an important initia tor in the adhesion of lymphocytes to the epidermis. These results seem to indicate that peripheral expression of inter cellular adhesion molecule 1 can be involved as a crucial early molecular event in the process of annular formation [5]. Another unusual variant of lichen planus is atrophic lichen planus, which occurs after the resolution of long time lesions of lichen planus [6, 7| and is interpreted as a result of thinning of the epidermis and fibrosis of the papil Received: May 28, 1993 Accepted: October 7, 1993 lary dermis [8].…”
mentioning
confidence: 83%
“…The proliferation potential is greatly reduced and bacterial processing proceeds up to antigenic peptide levels. Cell‐mediated immune responses with memory CD4+ Th‐1 and CD8+ T‐lymphocyte expression may result and lead to epithelioid cell granuloma formation 14–16 or a lichenoid reaction 60–67 . CD4+ Th‐1 lymphocyte stimulation induces interferon‐γ (IFN‐γ) and interleukin‐2 (IL‐2) release, which promotes and accelerates phagolysosome processing within newly infected macrophages.…”
Section: Introductionmentioning
confidence: 99%